Ethnobotanical study on the Genus Pandanus L. f. in certain areas in Java, Indonesia - WARDAH WARDAH; FRANCISCA MURTI SETYOWATI (Society for Indonesian Biodiversity, 2009)
There were two species of Pandanus recorded in Java, Pandanus amaryllifolius Roxb. and Pandanus tectorius Sol. The leaf of P. tectorius is commonly harvested as source of handicraft materials, while P. amaryllifolius is for culinary aromatic purposes only. The pandan kunyit (P. tectorius Sol.) in Bangkalan and pandan jeksi (P. tectorius Sol. var. samak Werb.) in Kebumen (Central Java) are the best resource for plaiting industry. Prospect of Pandanus plaiting can rise the income of farmers in the village and rise foreign exchange depend on how to fulfill the best pandan and its processing. It is hoped the good relation between farmers and government to sustain and develop the pandan production.Key words: ethnobotany, Pandanus, uses, Java.